MEMAKNAI HUKUMAN MATI BAGI KORUPTOR BERDASARKAN FILSAFAT HUKUM - Diya Ul Akmal; Syafrijal Mughni Madda (SUPREMASI HUKUM, 2021)
The existence of the death penalty for corruptors in Prevailing Laws is part of efforts to eradicate corruption. Corruption is considered to have become entrenched so that extraordinary efforts are needed to deal with it. The firmness of sanctions is expected to give fear to everyone when they want to commit corruption. There are differences of opinion regarding the provision of the death penalty. To minimize these differences, a philosophical study is needed to understand them. This study uses a normative juridical method with a statutory approach. The data used is secondary data obtained through literature study. The Constitution has explicitly regulated human rights and their limitations. These restrictions are carried out when someone violates the rights of another person. Corruption is a systematic act that harms the wider community. So that the death penalty for corruptors is a form of providing justice to the community. Law enforcement officers must have the courage to apply the death penalty but must be adjusted to the provisions contained in the Legislation.